Role of Breastfeeding and Onset of Atopic Dermatitis in Children Patient: a Cross Sectional Study - Arridha Hutami Putri; Sri Wahyuni Purnama; Irma Damayanti Roesyanto (Universitas Muhammadiyah Sumatera Utara, 2020)
Abstract: Atopic dermatitis (AD) is a multifactorial disease belongs to the